The development of morphological characterization magazine of Terigas tangerines (Citrus reticulata Blanco) at Mekarsari citrus picking tour, Blitar regency - Pratiwi, Yulian Pratiwi; Agustin, Haslinda Yasti (Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2021)
This study aims to develop learning media in the form of magazines resulting from the morphological characterization of the Keprok Terigas citrus plant and to determine the level of feasibility. This type of research is research and development (R&D), with the first phase of qualitative research aiming to determine the morphological characterization of the Terigas Tangerine plant (Citrus reticulata Blanco). Data collection using observation and documentation methods. The second stage is the development of the magazine learning media product using the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research was only carried out until the implementation stage. The results of the first stage of research, namely the morphological characterization of citrus plants with tree stature and dark brown taproots. The stem is cylindrical in shape, the direction of growth is straight (slightly bent on top), the texture is strong and sturdy, and the color is brownish green. The leaves are compound, oval-shaped elongated, the base of the leaves is blunt, the tips of the leaves are pointed, the edges of the leaves are serrated, the upper surface is shiny, and the lower surface is rough, and the leaves are green. The flowers include compound flowers with a complete arrangement of yellowish white, and have two sexes, namely stamens and pistils. The flowers on this plant have the formula (♀*K5, C5, A16, G1). The fruit is a single true fruit that is fleshy, round and greenish yellow in color, and the seeds are oval-shaped yellowish white. The results of the second stage, namely research on the morphological characterization of the Terigas Tangerine plant (Citrus reticulata Blanco) was developed as a magazine, and validated by material experts, media experts and lecturers in Plant Anatomy and Morphology courses, each obtained a percentage of 76.4% (decent), 95% (very decent), and 85.2% (very decent). The results of the student legibility test on the feasibility of the magazine learning media obtained an average percentage score of 91.5%, which stated that this magazine was suitable to be used as one of the learning media to study Plant Anatomy and Morphology courses.